2021
DOI: 10.3390/joitmc7010017
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation during Web Surfing: Topics of Interest and Rejection by Latin American College Students

Abstract: The university is currently involved in complex processes of open innovation through permanent dialogue with institutions and companies in the economic, social, and political fields. Professors, researchers, students, and other members of the institution take part in these processes. This is a phenomenon that has emerged in today’s network society due to digitalization and globalization. It is therefore essential, in this context of open innovation, to know the behaviors, habits, consumption, or lifestyles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
2
13
0
1
Order By: Relevance
“…These results appeared to be consistent with that of Naveed et al [8], who also reported the everyday life information needs of resident university students at the University of the Punjab were related to their health, socio-economic, cultural, technological, and legal issues. Similar results were reported by Gómez-Galán et al [42], who found that Latin American college students were interested in such everyday topics for open innovation.…”
Section: Discussionsupporting
confidence: 89%
“…These results appeared to be consistent with that of Naveed et al [8], who also reported the everyday life information needs of resident university students at the University of the Punjab were related to their health, socio-economic, cultural, technological, and legal issues. Similar results were reported by Gómez-Galán et al [42], who found that Latin American college students were interested in such everyday topics for open innovation.…”
Section: Discussionsupporting
confidence: 89%
“…Some previous studies have also shown this (Gómez-Galán et al, 2020a;Gómez-Galán et al 2020b;Gómez-Galán et al, 2021). This has also been determined in some countries analyzed in this research, such as Spain (Garrote et.…”
Section: Discussionsupporting
confidence: 84%
“…It is also worth stressing that growing Internet consumption and the advantage of online life over everyday life may lead to psychological and/or even psychiatric disorders [161], such as depression and anxiety, as well as harassment. Internet addiction has many similarities with addiction to the consumption of toxic substances.…”
Section: Covid-19 Pandemic and Distance Teaching Realitymentioning
confidence: 99%